Peculiarities of «Techno-R» Technology During Teaching French Language Grammarian Skills - K. Kuzmina, Elena; N. Vassilie, Valentina; I. Galeeva, Gulnara; Leblanc, CÃ©cile (International Journal of Engineering and Technology, 2018)
The article describes the methodological basis of "Techno-R" technology, its substantive and procedural aspects. In the content aspect the technology "Techno-R" consists of eight blocks designed to develop the communicative competence of trainees. The communicative language competence consists of four blocks - vocabulary, grammar, phonetics, spelling, and speech is also represented by four blocks - speaking, listening, reading and writing. Each block has its own peculiarities in the content aspect, but the procedural aspect of the technology is one for all blocks. The technology includes the setting of an educational task, an indicative basis for speech actions, task performance training, carrying out control actions and competence level determination that is being developed. The authors set out an experimental study to teach grammatical skills of French language on the basis of the technology being developed. Empirically obtained data, subjected to statistical processing on the basis of Student’s t criterion, demonstrate the value of T criterion > 3.3, which indicates the reliability of the conclusions about Techno-R technology effectiveness. In the article the authors made conclusions about the peculiarities of the abovementioned technology, its correctional nature, the combination with the known pedagogical technologies, the availability of language problems, creating the conditions for the transfer of grammatical skills and the production of student self-esteem in language competence development that stimulates the motivation of learning.